ENTREPRENEURIAL CULTURE IN THE REGIONAL MUSEUMS OF HISTORY IN BULGARIA – CASE STUDY OF REGIONAL MUSEUM OF HISTORY VARNA - Genka Rafailova; Todor Dyankov; Krasimira Yancheva (Business & Management Compass, 2024)
The present study aims to define and discuss opportunities for developing entrepreneurial culture regarding the management of regional museums of history in Bulgaria, based on a case study of the Regional Museum of History Varna (RMH Varna), Bulgaria. The challenging environment for the successful functioning of public cultural institutions leading to a steady flow of finances, visitors, and community support today and in the future insists on a relevant change in management approach. Museums, subsidized by the government and having key research and conservation activities, need to be more entrepreneurial-oriented despite the controversy with their social mission and limits determined by their legal status. The study explains the entrepreneurial culture in museums as public cultural institutions from an interdisciplinary view. It follows the theoretical explanation of organizational culture, creative entrepreneurship, and hybrid experience. The model of entrepreneurial culture is constructed by developing the idea of combining characteristics of traditional, research-based, and modern visitor-oriented museums. The paper discusses the environment and vision for the implementation of the entrepreneurial culture in the management of regional museums of history in Bulgaria in the course of a case study of RMH Varna.